Multidimensional separation of tryptic peptides from human serum proteins using reversed‐phase, strong cation exchange, weak anion exchange, and fused‐core fluorinated stationary phases2. Issue 21 (13th September 2013) - Boichenko, Alexander P.; Govorukhina, Natalia; van der, Ate G. J.; Bischoff, Rainer
<x xml:space="preserve">Abstract</x> Proteome profiling of crude serum is a challenging task due to the wide dynamic range of protein concentrations and the presence of high‐abundance proteins, which cover >90% of the total protein mass in serum. Peptide fractionation on strong cation exchange, weak anion exchange in the electrostatic repulsion hydrophilic interaction chromatography (ERLIC) mode, RP C18 at pH 2.5 (low pH), fused‐core fluorinated at pH 2.5, and RP C18 at pH 9.7 (high pH) stationary phases resulted in two to three times more identified proteins and three to four times more identified peptides in comparison with 1D nanoChip‐LC–MS/MS quadrupole TOF analysis (45 proteins, 185 peptides). The largest number of peptides and proteins was identified after prefractionation in the ERLIC mode due to the more uniform distribution of peptides among the collected fractions and on the RP column at high pH due to the high efficiency of RP separations and the complementary selectivity of both techniques to low‐pH RP chromatography. A 3D separation scheme combining ERLIC, high‐pH RP, and low‐pH nanoChip‐LC–MS/MS for crude serum proteome profiling resulted in the identification of 208 proteins and 1088 peptides with the lowest reported concentration of 11 ng/mL for heat shock protein 74.